The ogress and the orphans - Barnhill, Kelly Regan (Algonquin Young Readers, 2022)
When a child goes missing from the Orphan House in the town of Stone-in-the-Glen, the mayor suggests the kindly Ogress is responsible, but the orphans do not believe that and try to make their deluded neighbors see the real villain among them.